2014
DOI: 10.1177/0300985814552108
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Epicardial Fibrosis in Mice With Sternal Segment Dislocation

Abstract: We report coincident sternal segment dislocation and focally extensive right ventricular epicardial fibrosis observed during routine histopathology evaluation of C57BL/6N mice as part of a high throughput phenotyping screen conducted between 4 and 16 weeks of age. This retrospective case series study was conducted to determine whether cardiac fibrosis was a pathological consequence of sternal segment dislocation. We identified sternal segment dislocation in 51 of the total 1103 mice (4.6%) analyzed at 16 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Conversely, there are reports of sporadic, low-level defects in inbred lines which are likely due to oligogenic or polygenic effects and exhibit variable penetrance thus only observed or measured in a proportion of the population of an inbred colony [3]. These include complex behaviours such as aggression [4], hyperactivity [5], morphological anomalies such as sternal segment dislocation [6] and developmental defects such as hydrocephalus (https://www.jax. org/news-and-insights/2003/july/hydrocephalus-in-laboratory-mice).…”
Section: A1111111111 A1111111111 A1111111111 A1111111111 A1111111111mentioning
confidence: 99%
“…Conversely, there are reports of sporadic, low-level defects in inbred lines which are likely due to oligogenic or polygenic effects and exhibit variable penetrance thus only observed or measured in a proportion of the population of an inbred colony [3]. These include complex behaviours such as aggression [4], hyperactivity [5], morphological anomalies such as sternal segment dislocation [6] and developmental defects such as hydrocephalus (https://www.jax. org/news-and-insights/2003/july/hydrocephalus-in-laboratory-mice).…”
Section: A1111111111 A1111111111 A1111111111 A1111111111 A1111111111mentioning
confidence: 99%
“…Besides humans, mesothelial hyperplasia is reported in monkeys (Sato et al, 2012;Winn et al, 2018), dogs (Milne et al, 2018), cats (Weiss and Scott, 1981), rabbits (Dalton and Chun, 1966), horses (Hoon-Hanks et al, 2016), cattle (Gold-smith and Adaska, 2020), rats (Slater et al, 1991), and mice (Adissu et al, 2015).…”
Section: Mesothelial Hyperplasiamentioning
confidence: 99%
“…However, the finding of homozygous deletion of p16 by fluorescence in situ hybridization (FISH) or the loss of BRCA1 associated protein 1 (BAP1) by immunohistochemistry is found only in mesotheliomas (Husain et al, 2018). Using gene-expression-based tests for BAP1 and p16 analysis might become a reliable tool to distinguish benign from malignant mesothelial proliferations (Ali et al, 2020).…”
Section: Discrimination Between Benign and Malignant Mesothelial Altementioning
confidence: 99%
“…With physiological phenotyping, findings may not fully contribute to determining the cause of morbidity or death without histopathological confirmation, and indeed important phenotypes may be entirely missed. 2,3,16 For example, a recent study by Adissu et al 2 on a random selection of mutants from the International Mouse Phenotyping Consortium (IMPC) primary phenotyping pipeline found that histopathology added correlating morphological data in 63% of cases for which the primary physiological screen detected a phenotype, and 14% presented significant histopathology findings that were not predicted by the standard primary physiological screen. On the other hand, if pathology findings do not discover the cause of illness, other phenotype data may aid in the determination of the cause of morbidity and mortality.…”
Section: Integration Of Pathology Data With Other Phenotype Datamentioning
confidence: 99%